2007
DOI: 10.1007/s10897-006-9051-6
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Utilization of Cancer Genetic Counseling Services Using a Patient Navigator Model

Abstract: Rarely has utilization of genetic counseling for Hereditary Breast and Ovarian Cancer (HBOC) been studied separately from utilization of testing. At Kaiser Permanente Colorado, consistently only 30% of all members referred for HBOC attend genetic counseling. To increase the volume of genetic counseling appointments, a patient navigator approach was pilot tested in a randomized-controlled trial over 3 months. A total of 125 members were referred for HBOC genetic counseling (55 randomized to PN, 70 randomized to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 17 publications
1
46
0
1
Order By: Relevance
“…[32][33][34][35][36][37] Such programs are designed to help patients navigate complex health care systems. They may have the flexibility to help patients address transportation and financial barriers, for example, by arranging escorts, accompanying groups of patients who can be scheduled together, and arranging free or affordable access to colonoscopy preparation medications kept on site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[32][33][34][35][36][37] Such programs are designed to help patients navigate complex health care systems. They may have the flexibility to help patients address transportation and financial barriers, for example, by arranging escorts, accompanying groups of patients who can be scheduled together, and arranging free or affordable access to colonoscopy preparation medications kept on site.…”
Section: Discussionmentioning
confidence: 99%
“…This is another area where navigator systems have proven useful. [32][33][34][35][36][37] They can play a motivational role by forming relationships with patients, calling and meeting with them, and not allowing the issue of CRC screening to fall off the patient's "radar." This can help to overcome the inertia, which keeps many otherwise willing patients from getting screened.…”
Section: Discussionmentioning
confidence: 99%
“…Results showed patient navigators improved screening rates, diagnostic test participation, or genetic counseling (Dignan et al, 2005; Jandorf, Gutierrez, Lopez, Christie, & Itzkowitz, 2005; Rahm, Sukhanova, Ellis, & Mouchawar, 2007; Tingen et al, 1998; Weinrich et al, 1998). Navigation led to better adherence to ongoing treatment (Battaglia et al, 2007; Ell, Vourlekis, Lee, & Xie, 2007; Ferrante, Chen, & Kim, 2008; Giese-Davis et al, 2006).…”
Section: Integrated Care and Patient Navigatorsmentioning
confidence: 99%
“…Initial research demonstrates that patient navigators are associated with improved outcomes for screening, follow-up, lower clinical stages of presentation, and higher levels of patient satisfaction (Ell et al, 2002;Freeman et al, 1995;Frelix, Rosenblatt, Solomon, & Vikram, 1999;Weinrich et al, 1998), with a significant improvement in preventative service utilization (Freeman et al, 1995;Frelix et al, 1999;Gardner, Arya, & McAllister, 2005;Rahm, Sukhanova, Ellis, & Mouchawar, 2007;Weinrich et al, 1998). For example, Freeman et al (1995) demonstrated that use of a PN program in an inner-city clinic yielded an 87.5% biopsy rate after an abnormal mammogram versus a 56.6% biopsy rate in a clinic that did not use a PN program (Freeman et al, 1995).…”
mentioning
confidence: 99%